(untitled) (TAJ: Journal of Teachers Association, 2018)
Non-Toxic multi-nodular goitre is one of the common presentations of various thyroid diseases. A sizable portion of multi-nodular goitre turns into malignancy over time. This cross-sectional study was conducted in RMCH and different clinics of Rajshahi City to determine the incidence and types of various thyroid malignancies in non-toxic multi-nodular goitres. Among the total cases, 43% of the patients were in the age group of 31-40 years and majority (81%) of whom were female. 52% of the patients had a history of thyroid swelling for 1-5 years and 55% of the patients had goitre size ≤ 15 cm2. Sub-total thyroidectomy was the commonest operation performed and all the resected specimens were sent for histopathological examinations, which demonstrates that 13% of the multi-nodular goitres had malignancies with papillary and follicular carcinoma ratio 5:1. This study did not reveal any significant association of malignancies with age and sex and goitre size also not influence the presence of malignancy. However, it was observed that the mean duration of thyroid swelling in patients who developed malignancy was significantly higher (8.6 years) than that of patients who did not experience any malignant change (5.7 years). TAJ 2016; 29(2): 16-20